STRATEGIES AND TECHNIQUES FOR DEVELOPING SPEAKING - Rahimjonova Xumora Ziyovuddin qizi (Journal of new century innovations, 2024)
Abstract: Developing strong speaking skills is crucial for effective communication in both personal and professional settings. This article examines various strategies and techniques to improve speaking abilities, emphasizing practical methods that can be incorporated into everyday practice. Oral language is a crucial skill for students to master for both social and academic achievement. Students use this skill constantly throughout the day to follow and give instructions, make requests, ask questions, absorb new information, and interact with peers. It is regarded as one of the fundamental elements of language proficiency.